Gambaran Pengetahuan Ibu Nifas Normal Tentang Senam Kegel Di Ruang 7 RSUD dr. Soekardjo Tasikmalaya - Asep Riyana Asry; Anwar Masalikil Huda (Poltekkes Kemenkes Tasikmalaya, 2022)
The background of this study is that during the postpartum period, changes occur in the mother, baby and family, both physiologically, emotionally and socially, so that the care and encouragement provided by professional health workers helps to form an interconnected response between the three during this time. Kegel exercise is one of the exercises that can be done or trained during the puerperium for mothers who give birth vaginally. The Porpuse of this study aims to know the description of normal postpartum mothers knowledge about Kegel exercises consist of understanding, purpose, benefits, principles and procedures of Kegel exercises in Room 7 RSUD dr. Soekardjo. The Research Methode is a descriptive study with univariate analysis of the data types that generate the frequency distribution and percentage data. The total sample of 77 respondents with a sampling technique that accidental sampling. The Results showed that postpartum mothers have less knowledge about Kegel exercises as much as 37 respondents with a percentage of 48,1. Suggestions from this study are that health workers in the postpartum care room need to improve health services, both providing health education and proper Kegel exercises so that they can increase the knowledge, interest, and participation of postpartum mothers for Kegel exercises.